Micro‐ and macrovascular complications and risk factors for foot ulceration and amputation in individuals receiving dialysis with and without diabetes. Issue 1 (17th October 2021) - Kofod, Dea Haagensen; Almdal, Thomas Peter; Sørensen, Vibeke Rømming; Feldt‐Rasmussen, Bo; Hornum, Mads
Abstract: Introduction: This study examined the prevalence of microvascular and macrovascular complications in people receiving dialysis with and without diabetes and investigated independent risk factors for foot ulcers and lower‐extremity amputations. Methods: We performed a cross‐sectional study of 119 individuals with diabetes and 219 individuals without diabetes receiving chronic dialysis during June 2019 at the Department of Nephrology, Rigshospitalet, University of Copenhagen, Denmark. Effects of diabetes and other risk factors were assessed by log‐binomial regression. Prevalence data were compared with a historical control group of 38 individuals with diabetes receiving dialysis examined in 2004 in the same department. Results: We found that persons with diabetes had a twofold higher risk ratio of current (unadjusted risk ratio 2.2 [95% CI 1.1, 4.7]) and previous foot ulcer (2.5 [1.7, 3.7]) and a fourfold higher risk ratio of lower‐extremity amputation (4.2 [2.1, 8.6]) in comparison with persons without diabetes (all p  < .05). Furthermore, persons with diabetes had a 70% increased risk ratio of myocardial infarction (1.7 [1.0–2.8], p  = .041). In multivariable‐adjusted analysis, current foot ulcer was independently associated with previous foot ulcer (adjusted risk ratio 4.0 [95% CI 1.8, 8.9]), while lower‐extremity amputation was independently associated with diabetes (3.8 [1.8, 8.2]) and male sex (4.1 [1.5, 11.3]) (all p  < .01). Conclusions: Individuals with diabetes receiving dialysis had a higher prevalence of foot ulcer, lower‐extremity amputation and myocardial infarction compared to individuals without diabetes. Previous foot ulcer was the most important risk factor for current foot ulcer, while diabetes and male sex were important risk factors for lower‐extremity amputation. Abstract : Over the past decades, there has been a general improvement in the prognosis of people with diabetes; however, it is unclear what the consequences of these improvements are in relation to complications among people receiving dialysis. This study examined the prevalence of micro‐ and macrovascular complications in people receiving dialysis with and without diabetes, and found that individuals with diabetes had a higher prevalence of foot ulcer, amputation and myocardial infarction compared to individuals without diabetes.